2007
DOI: 10.1111/j.1600-0501.2006.01314.x
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of the trabecular bone behavior to porous electrostatic spray deposition‐derived calcium phosphate coatings

Abstract: Crystalline carbonated hydroxyapatite ESD-coated implants positively influenced the biological performance compared with Ti control implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…The characteristic network structure of the films fabricated in this present work can also be observed for films formed using the ESD method [24][25][26][27]; however, the network structure on the surface of the present films (10-15 μm) is twice as large as that of the films formed by the ESD method (5-7 μm) [40]. The rounded particles evident on the surfaces of the films (Figs.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The characteristic network structure of the films fabricated in this present work can also be observed for films formed using the ESD method [24][25][26][27]; however, the network structure on the surface of the present films (10-15 μm) is twice as large as that of the films formed by the ESD method (5-7 μm) [40]. The rounded particles evident on the surfaces of the films (Figs.…”
Section: Discussionsupporting
confidence: 54%
“…Recently, Leeuwenburgh et al [24,25] and Siebers et al [26,27] reported a CA coating produced using electrostatic spray deposition (ESD) that was originally developed to fabricate thick ceramic films for solid electrolytes [28]. Amorphous films deposited by ESD on a substrate heated to 470°C converted to crystalline CA films after 15 s of heat treatment above 700°C in air.…”
Section: Introductionmentioning
confidence: 98%
“…Example is calcium phosphate (CaP) coating, which is able to increase the adhesion and activation of bone cells on the implant surface [14]. Also, histological studies confirmed that indeed CaP coated implants evoke an increased bone adaptation compared to non-coated implants [15,16]. This beneficial biological effect of CaP coatings is supposed to be due to the chemical similarity between this synthetic material and the mineral component in natural bone [17].…”
Section: Introductionmentioning
confidence: 82%
“…While model biomaterial surfaces to control ligand presentation (e.g., self-assembled monolayers on gold or silicon) have been extensively studied, the development of robust coating technologies for tunable presentation of bioactive factors on materials approved for biomedical implantation has been particularly challenging. Recent bioactive implant surface treatments on Ti, including porous hydroxyapatite, collagen I, and calcium phosphate co-precipitated with various other biological ligands, have augmented aspects of bone healing compared to unmodified Ti in various animal models [27][28][29]. However, these strategies lack control over protein adsorption, ligand presentation and density, and surface stability.…”
Section: Discussionmentioning
confidence: 99%